Peta hubungan topik penelitian skripsi IPB University lulusan tahun 2020 - Abdul Saleh; Sri Rahayu (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. Agricultural progress cannot be separated from research activities carried out by researchers and students. It is suspected that the thesis research topics in IPB undergraduate theses are thought to be related to one another. This study aims to determine the relationship of the research topics of the IPB undergraduate theses in 2020. Research methods. This research is a mixed method research. The data collected by purposive sampling technic with a 2020 limit. The data was retieved from IPB repocitory. Data analysis. The data were tabulated and analyzed using the VOSviewer to generate maps relationships between keywords. Results and Discussion. Co-word analysis of controlled keywords found 181 keywords. Co-word analysis with a limitation of three keyword occurrences found 120 related keywords grouped into 10 clusters. Co-word analysis of the keywords formed by the author found 10,943 keywords. The ten occurrence limit found 81 keywords in 11 clusters. Similar research topics were found in at least two faculties. Conclusion. The research topics of IPB's thesis were spread into 120 topics with 10 clusters having close relationships. It was found that there were similarities in research topics between one faculty and another.